2010
DOI: 10.1016/j.juro.2009.08.154
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients With Primary Upper Urinary Tract Cancer Receive Prophylactic Intravesical Chemotherapy After Nephroureterectomy?

Abstract: Intravesical instillation of epirubicin or mitomycin C appears to be well tolerated and effective for preventing bladder recurrence and prolonging time to first bladder recurrence. Patients should receive prophylactic intravesical chemotherapy after nephroureterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 24 publications
1
50
0
Order By: Relevance
“…A total of 7 trials focused on this topic and potentially met the selection criteria [21,22,23,24,25,26,27]. Two trials were excluded because some patients underwent radical nephrectomy instead of nephroureterectomy [26,27] and because some patients received intravesical instillation before surgery in one trial [26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 7 trials focused on this topic and potentially met the selection criteria [21,22,23,24,25,26,27]. Two trials were excluded because some patients underwent radical nephrectomy instead of nephroureterectomy [26,27] and because some patients received intravesical instillation before surgery in one trial [26].…”
Section: Resultsmentioning
confidence: 99%
“…Two trials were excluded because some patients underwent radical nephrectomy instead of nephroureterectomy [26,27] and because some patients received intravesical instillation before surgery in one trial [26]. Five trials were retained, including four published articles [21,22,23,25] and one meeting program abstract from the AUA annual meeting [24]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al [22] reported the effectiveness of adjuvant intravesical chemotherapy right after NUx. They concluded that adjuvant intravesical chemotherapy could decrease the risk for recurrence and extend the time until the first recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…However, approximately 20-50% of patients experience bladder recurrence after RNU [1] . Cur-rently, prophylactic intravesical chemotherapy after RNU is one of the few available treatments effective in preventing secondary bladder cancer (Bca), but the optimal chemotherapy regimen and the initial time of instillation remain controversial [3][4][5] . Moreover, it is improper for all patients to receive the same intravesical chemotherapy regimen because this would lead to excessive treatment for low-risk patients.…”
Section: Introductionmentioning
confidence: 99%